Sex differences in perception of invisible facial expressions - Sang Wook eHong (Frontiers in Psychology, 2015)
Previous research indicates that women are better at recognizing facial expressions than men. In the current study, we examined whether this female advantage in the processing of facial expressions also occurs at the unconscious level. In two studies, participants performed a simple detection task and a 4-AFC task while faces were rendered invisible by continuous flash suppression (CFS). When faces with full intensity expressions were suppressed, there was no significant sex difference in the time of breakup of suppression (Study 1). However, when suppressed faces depicted low intensity expressions, suppression broke up earlier in men than women, indicating that men may be more sensitive to facial features related to mild facial expressions (Study 2). The current findings suggest that the female advantage in processing of facial expressions is absent in unconscious processing of emotional information. The female advantage in facial expression processing may require conscious perception of faces.